2014
DOI: 10.1080/15421406.2013.871847
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Mechanism in a Linear Non-Conjugated Trimethylsilyl-Acetylene Molecule: Tunneling Through Localized States

Abstract: The conductance properties of 1,3-(trimethylsilyl)-1-tridecene-6,12-diyne, a nonconjugated trimethylsil-acetylene molecule have been investigated both experimentally and theoretically. Based on scanning tunnelling spectroscopy experiments, a discussion on the mechanisms controlling the charge transfer through this linear molecule is carried out. A specific property of the studied molecule is that it contains localized molecular orbitals. The shifts of the MOs energy levels caused by the applied voltage as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…These ndings are in excellent agreement with the data obtained by Fichou et al from SAMs of TMSE functionalised unsaturated hydrocarbons on at gold substrates. 28,29 The Fichou group report SAMs exhibit excellent registry with the underlying gold surface, consistent with the positioning of the TMSE group at the hollow sites. The higher binding energy calculated here is consistent with the stability of the lms and the signicant binding energy is consistent with the evidence of pit-etching.…”
Section: Dft Calculationsmentioning
confidence: 71%
See 2 more Smart Citations
“…These ndings are in excellent agreement with the data obtained by Fichou et al from SAMs of TMSE functionalised unsaturated hydrocarbons on at gold substrates. 28,29 The Fichou group report SAMs exhibit excellent registry with the underlying gold surface, consistent with the positioning of the TMSE group at the hollow sites. The higher binding energy calculated here is consistent with the stability of the lms and the signicant binding energy is consistent with the evidence of pit-etching.…”
Section: Dft Calculationsmentioning
confidence: 71%
“…23 Theoretical studies of molecules with the trimethylsilylethynyl moiety contacted to gold electrodes have been also carried out. 28 Using a semi-phenomenological model based on kinetic theory of charge transmission 29 the authors found a rather good agreement between theory and experiment with just three adjustable parameters (the transmission gap DE +j and the width parameters G (L) j and G (R) j ), and a limited interaction between the molecular orbitals and the substrate.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other functional groups, including amines, 12 carboxylic acids, [12][13][14] dithiocarboxylic acids, 15 esters, 16 pyridyl, [17][18][19][20] cyano, 21,22 isocyano, 23,24 isothiocyanate, 25 nitro, 21 methylselenide, 26 methylthiol, 26 dimethylphosphine, 26 ethynyltrimethylsilane, [27][28][29][30][31][32][33] viologens 34 and fullerenes 13,35 have been studied as potential molecule-contacting groups for various metal surfaces. However, these metal|molecule contacts are also characterized by fluxional bonds to the surface leading to structural rearrangements of the films, surface etching and reforming, and, in the case of molecular electronic studies, the observation of multiple conductance signals, stochastic on-off switching of the molecule-metal contact, high contact resistance and other issues.…”
Section: Toc Graph Introductionmentioning
confidence: 99%
“…8 Building on the success of measurements of molecular electronic characteristics in test platforms, the next signicant challenge to be addressed before molecular electronics can be considered a truly viable and scalable technology is the construction of robust and reliable metal-molecule contacts. A wide variety of molecular functional groups have been tested as contacting groups for various substrates (principally gold), including thiols, 9,10 amines, 11,12 carboxylic acids, [12][13][14] dithiocarboxylic acids, 15 esters, 16 pyridyl, [17][18][19] cyano, 20,21 isocyano, 22,23 isothiocyanato, 24 nitro, 20 methylselenide, 25 methylthiol, 25 dimethylphosphine, 25 trimethylsilane, [26][27][28][29][30][31] fullerenes, 32,33 etc. However, most of these metal-molecule contacts exhibit uxional functional-group to surface bonds leading to stochastic on-off switching, structural rearrangements of the leads, multiple distinct types of metal-molecule contact arising from molecule binding to different surface structures resulting in multiple and signicantly different conductance signals, or high contact resistance.…”
Section: Introductionmentioning
confidence: 99%